SEBAB DAN AKIBAT SERTA PERTANGGUNGJAWABAN HUKUM TERHADAP KASUS SALAH TANGKAP (ERROR IN PERSONA) DI WILAYAH HUKUM KEPOLISIAN RESOR KUPANG KOTA - Nainatun, Maryani Tefliana; Amalo, Heryanto; Kian, Darius A (Petitum Law Journal, 2024)
Basically, problems with the application of the presumption of innocence in criminal cases still often occur in the resolution of criminal cases. This also makes it possible for victims to be wrongly arrested due to a lack of evidence but when they are arrested. This research is empirical juridical research, where this research was carried out at the Kupang City Police Department. The data obtained in this research is qualitative data, using interview guidelines with informants and respondents, then the data is processed into qualitative descriptive. The results of this research show that: (1) the causes of cases of victims of wrongful arrest (error in person) in the jurisdiction of the Kupang City Police, which are more directly related to the internal factors of each member, namely regarding their knowledge, skills, and attitudes and behavior as a member police. (2) The consequences for the victim of wrongful arrest and violence and abuse by individuals include losses experienced by the victim, these losses are material losses and immaterial losses. (3) Responsibility for victims of wrongful arrest and abuse by police officers can be dealt with criminally or code of ethics, victims can also demand legal protection such as rehabilitation or restoration of their good name as well as compensation in the form of compensation.